Post-traumatic syndrome - Harsono, Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Post-traumatic syndrome is a constellation of symptoms that developed in a person usually following a relatively minor head injury. It can grossly in capacitating for the patient and can develop a chronicity that makes it almost a change in personality. The commonest symptoms are headache, and dizziness; but impairment of sleep, decreased concentration and libido, anxiety, depression, irritability and sensitivity to noise are also seen.The cause of the syndrome is a ,contentious issue. The question whether it is primarily of psychological or organic origin remains unanswered in many cases. Organic or phychogenic, each symptom by itself is of little consequence, but in combination they may be disabling enough to prevent useful employment. Furthennore, the development of the syndrome of any head injury is not easy to be predicted.Key Words: post-traumatic syndrome headache neurotic personality depression amnesia